Effect of Immersion of Striped Catfish (Pangasionodon hypophthalmus) in Red Dragon Fruit Peel Solution (Hylocereus polyrhizus) on Gill and Kidney Histopathology - M. Taufik; Henni Syawal; Morina Riauwaty (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Red dragon fruit peel is a natural material with antibacterial potential against fish diseases. This study was conducted from July 2024 to June 2025 at the Laboratory of Fish Parasites and Diseases, Faculty of Fisheries and Marine Sciences, Universitas Riau. The aim was to determine the histopathology of gills and kidneys in striped catfish (Pangasionodon hypophthalmus) immersed in red dragon fruit peel extract and challenged with Aeromonas hydrophila. The experiment used a Completely Randomized Design (CRD) with five treatments and three replications: Kn (negative control), Kp (positive control, challenged with A. hydrophila), P1 (1 mL/L), P2 (1.5 mL/L), and P3 (2 mL/L). Immersion was applied three times at the beginning of rearing, followed by 46 days of culture. A challenge test was carried out on day 32, and gill and kidney samples were collected on days 30 and 14 post-challenge. Results showed that fish challenged with A. hydrophila exhibited gill damage, including hypertrophy, lamellar curvature, telangiectasis, and epithelial lifting, as well as kidney damage, including necrosis, hemorrhage, and cell degeneration. The best result was observed in treatment P2 (1.5 mL/L), which effectively reduced tissue damage and improved the histological structure of gills and kidneys in striped catfish